From the seat to the system: Re-designing a tram drivers' workstation combining technical and contextual aspects. (November 2018) - Nathanael, Dimitris; Marmaras, Nicolas
Abstract: Through the detailed account of a design case-study, the paper aims to demonstrate how the activity-oriented approach promotes a systems perspective in ergonomics interventions. Specifically, by presenting an activity-oriented re-design of a tram drivers' workstation, it is shown: (i) how technical and contextual aspects were jointly considered, (ii) how their combination affects workers' activity in a non-trivial manner, and (iii) how this system level view helped generate feasible and sustainable design solutions. First, the activity-oriented theoretical lens is briefly presented, followed by the analysis of the tram driving activity, emphasizing on drivers' efforts to compensate for the original work-system design flaws. Next, key elements of the re-design process are presented, through a concept map, combining technical and contextual aspects, coupled with an account of stakeholder debates and resolution processes. The paper ends with a discussion on the lessons learned, concerning the adopted approach for design interventions in real work situations. Highlights: The activity-oriented approach fulfils the need for a systems' perspective in ergonomic interventions. Activity-oriented interventions require the accord and participation of the affected working population. Design decisions should be based both on technical knowledge and on the social, organizational and financial context. To adopt design solutions, stakeholders need to genuinely understand the diverse system constraints.